Alcances y dimensiones del plagio en la narrativa de Alberto Laiseca: alrededor de Por favor ¡plágienme! - Fernández González, Carlos (Revista Chilena de Literatura, 2014)
Through the critical reading of Por Favor ¡Plágienme! (1991), a key text for understanding the aesthetic and creative universe of Alberto Laiseca, this article enquires into the unique approach that his narrative opens to the issue of plagiarism in contemporary literature. The article also postulates thinking Laiseca’s work in a tense –and parodic– relationship with the Argentinian literary tradition and its canon. This reading will operate on the central device of “Laisecan” literature, which consists on destabilizing available theoretical discourses over aspects that can be applied to his poetics, as the conceptual horizon of plagiarism. From here it will be possible to consider why a hegemonic literary criticism has had little dialogue with the work of someone who is, however, one of the most prolific contemporary writers of Argentinian literature.